2014
DOI: 10.2478/s13536-013-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and tensile properties of polypropylene/carbon nanotubes composites prepared by melt extrusion

Abstract: Polypropylene/carbon nanotubes (PP/CNTs) nancomposites were prepared with a single screw extruder by adding maleic anhydride-grafted poplypropylene (PP-g-MAH) as compatibilizer to polypropylene (PP) with different amounts of carbon nanotubes (CNTs) in the range of 0.1 -0.7 wt.%. Structure and morphology of the prepared samples were examined by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), polarizing light microscopy (PLM) and X-ray diffraction (XRD). The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Figure 2(a) and 2(b) reveal the improvements in the tensile strength and modulus with the addition of CNTs. Based on a study conducted by Li C. and co-workers, the degree of dispersion may be correlated to the mechanical performance of the polymer nanocomposite based on carbon nanotubes [24]. The elastic modulus of HDPE, HDPE-1CNT, and HDPE-2CNT was calculated to be 1200, 1500, and 1660 MPa, which represents a gradual improvement of 25% and 38% with the addition of 1 wt% and 2 wt% CNT, respectively.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2(a) and 2(b) reveal the improvements in the tensile strength and modulus with the addition of CNTs. Based on a study conducted by Li C. and co-workers, the degree of dispersion may be correlated to the mechanical performance of the polymer nanocomposite based on carbon nanotubes [24]. The elastic modulus of HDPE, HDPE-1CNT, and HDPE-2CNT was calculated to be 1200, 1500, and 1660 MPa, which represents a gradual improvement of 25% and 38% with the addition of 1 wt% and 2 wt% CNT, respectively.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…In other cases, very little number of studies have demonstrated that single screw extrusion may be employed for production of a polymer nanocomposite. For instance, Liu et al demonstrated that homogeneous dispersion of carbon nanotubes in a polypropylene matrix could be prepared with single screw extrusion method [24]. Based on the study, 1 wt% CNT concentration in Polypropylene achieved about 16% and 36% increase in the Young's Modulus and Tensile strength, respectively [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches have been proposed to prepare PP/CNT include melt mixing , in‐situ polymerization , and solution methods. Synthesis methods can directly influence nanotube dimension, dispersion, and interaction with the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Typical diffraction peaks at various 2θ are labelled with their corresponding crystal planes in figure. 20,21 Notably, the addition of the nanoparticles in the PP matrix decreased the broad diffraction peaks of pure PP at 2θ = 27.3 o and 41.7 o , which a indicates reduction in amorphous regions of the nanocomposites with possible increase in the crystalline domains. This could have also contributed to the improved thermal, mechanical, and thermomechanical properties of the nanocomposites in this study.…”
Section: Ftir and Xrd Analysesmentioning
confidence: 92%